2011
DOI: 10.1186/1757-7241-19-12
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro impairment of whole blood coagulation and platelet function by hypertonic saline hydroxyethyl starch

Abstract: BackgroundHypertonic saline hydroxyethyl starch (HH) has been recommended for first line treatment of hemorrhagic shock. Its effects on coagulation are unclear. We studied in vitro effects of HH dilution on whole blood coagulation and platelet function. Furthermore 7.2% hypertonic saline, 6% hydroxyethylstarch (as ingredients of HH), and 0.9% saline solution (as control) were tested in comparable dilutions to estimate specific component effects of HH on coagulation.MethodsThe study was designed as experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
23
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 35 publications
2
23
1
Order By: Relevance
“…In both cases, induced disorders are mainly dependent on fibrinogen-fibrin interactions as demonstrated by ROTEM®. The results are consistent with those of previously published studies (12)(13)(14), although the new contribution is the combination of both osmotic solutions with starch currently used in current practice.…”
supporting
confidence: 83%
“…In both cases, induced disorders are mainly dependent on fibrinogen-fibrin interactions as demonstrated by ROTEM®. The results are consistent with those of previously published studies (12)(13)(14), although the new contribution is the combination of both osmotic solutions with starch currently used in current practice.…”
supporting
confidence: 83%
“…We observed that the negative effect of 3% HS on functional fibrinogen--fibrin interaction was less than with 20% mannitol. All of the fluids that we have used in the study impair coagulation, depending on their molecular properties (especially the high osmolarity) and through haemodilution (12). These results indicated that whole-blood coagulation disorder induced by mannitol and HS is mainly dependent on the final fibrinogen--fibrin interaction, which results in a fibrin-poor clot.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, three different activators (InTEM, ExTEM and FibTEM) were used to examine the intrinsic and extrinsic coagulation pathways, platelet function and fibrinogen--fibrin interaction. Previous studies showed that HES, 20% mannitol and 3% HS caused coagulation impairment (7,11,12). When we searched the literature, we found two deficiencies:…”
Section: Discussionmentioning
confidence: 99%
“…Metabolic acidemia as encountered during hemorrhagic shock and/or excessive resuscitation with saline solution may also have significant effects on the coagulation system. This phenomenon has been shown in experiments in which hydrochloric acid (HCl) added to blood obtained from patients and titrated to a pH of 7.0 caused inhibition of thrombin propagation and a decrease in the activity of the Xa/Va, which was observed as prolonged clotting times on standard coagulation tests and abnormal patterns on thromboelastography [28,29]. Finally, dilutional thrombocytopenia, especially after massive blood transfusion and excessive administration of isotonic crystalloid solutions, is a common cause of perioperative coagulopathy [30].…”
Section: Why Cancer Patients May Bleedmentioning
confidence: 99%